The Impact of Advanced Age on Peri-Operative Outcomes in the Surgical Treatment of Cervical Spondylotic Myelopathy: A Nationwide Study Between 2001 and 2010. Issue 3 (February 2016) - Jalai, Cyrus M.; Worley, Nancy; Marascalchi, Bryan J.; Challier, Vincent; Vira, Shaleen; Yang, Sun; Boniello, Anthony J.; Bendo, John A.; Lafage, Virginie; Passias, Peter G.
Abstract : Study Design: Retrospective multicenter database review. Objective: The aim of this study was to evaluate national postoperative outcomes and hospital characteristics trends from 2001 to 2010 for advanced age CSM patients. Summary of Background Data: Recent studies show increases in US cervical spine surgeries and CSM diagnoses. However, few have compared national outcomes for elderly and younger CSM patients. Methods: A Nationwide Inpatient Sample (NIS) analysis from 2001 to 2010, including CSM patients 25+ who underwent anterior and/or posterior cervical fusion or laminoplasty. Fractures, 9+ levels fused, or any cancers were excluded. Measures included demographics, outcomes, and hospital-related data for 25 to 64 versus 65+ and 65 to 75 versus 76+ age groups. Univariate and logistic regression modeling evaluated procedure-related complications risk in 65+ and 76+ age groups (OR[95% CI]). Results: Discharges for 35, 319 patients in the age range of 25 to 64 years and 19, 097 at the age 65+ years were identified. Average comorbidity indices for patients at 65+ years were higher compared to the 25 to 64 years age group (0.79 vs. 0.0.44, P  < 0.0001), as was the total complications rate (11.39% vs. 5.93%, P  < 0.0001) and charges ($57, 449.94 vs. $49, 951.11, P  < 0.0001). Hospital course for aged 65+ patients was longer (4.76 vs. 3.26 days, P  < 0.0001). Mortality risk was higher in the 65+ cohort (3.38[2.93–3.91]), adjusted for covariates. 65+ patients had increased risk of all complications except device-related, for which they had decreased risk (0.61[0.56–0.67]). Patients 76+ years displayed increased hospital charges ($59, 197.60 vs. $56, 601.44, P  < 0.001) and courses (5.77 vs. 4.28 days, P  < 0.001) compared to those in the age group 65 to 75 years. These same patients presented with increased Deyo scores (0.83 vs . 0.77, P  < 0.001), had increased total complications rate (13.87% vs. 10.20%, P  < 0.001), and displayed increased risk for postoperative shock (6.34 [11.16–3.60], P  < 0.001), digestive system (1.92 [2.40–1.54], P  < 0.001), and wound dehiscence (1.71 [2.56–1.15], P  < 0.001). Conclusion: Patients aged 65+ years undergoing CSM surgical management have a higher mortality risk, more procedure-related complications, higher comorbidity burden, longer hospital course, and higher charges. This study provides clinically useful data for surgeons to educate patients and to improve outcomes.